The Effect Of Phyllanthus Debilis Extract On Dna Methylation And Mirna Regulation In Ht-29 Colorectal Cancer Cell Line - Zain, Siti Nur Dalila Mohd (2021)
Phyllanthus is one of the herbal plants that have been found to have anticancer property. Unfortunately, there is lack of study on the effect of the plant natural products on the epigenetics of cancer. Hence, this study was carried out to determine the effect of Phyllanthus debilis extract on DNA methylation and miRNA regulation in HT-29 colorectal cancer cell line. The study was started by determining the most suitable Phyllanthus species to be used in the epigenetic regulation of HT-29 cell line. Three species of Phyllanthus named Phyllanthus urinaria, Phyllanthus niruri and Phyllanthus debilis were used. The phytochemicals of each Phyllanthus species were then extracted using 100% methanol and 100% water. The extracts were then tested for Total Phenolic Content (TPC) and Total Flavonoid content (TFC) and the antioxidant activities of the plant extracts using DPPH and ABTS assays. Then, the extracts were screened with HPLC to detect the presence of targeted compounds. The therapeutic index of each Phyllanthus extract was then measured on cancer cell lines (breast and colorectal cell lines) versus normal cell line (normal breast cell line). P. debilis methanolic extract showed highest therapeutic index when compared to other extracts. P. debilis methanolic extract was then used for further study to investigate its mechanisms in regulating DNA methylation, gene and miRNA expressions in HT-29 cell line that led to the cancer cell death.